A translation of Katha Upanishad by Paul Ritter: an historico-philosophical context - Zavgorodnij, Yuriy (Actual Problems of Mind, 2017)
The paper presents a comparative analysis of the manuscript and published versions of a Katha Upanishad translation undertaken by P. Ritter. By considering the original text of Katha Upanishad as well as its various translations, the author points out some further prospects for a more adequate translation of ancient Indian writings and their better understanding.